Complex program of activation of psychological determinants of the following of frustration statuss of different age groups (Actual Problems of Psychology in Educational Institutions, 2019)
The goal and the process of implementation of the main tasksof the integrated programme of the activation psychological determinants ofovercome the frustrating conditions of the students of different age groups.Revealed the main regularities of the predictor structure of the frustratingconditions of the students of different age groups. A series of the psychologicalexercises was presented and aimed at constructivization of the profiles offrustration response of the students in three age samples (younger students,adolescents, youths). The main factors of transformation the determinants of theovercoming frustration are the reducing anxiety, the formation of internal locusof the control, the positive self and the individual character traits, increase thelevel of adaptation and development of the constructive styles of behavior in thefrustrating situations.
Keywords: frustration states, determinants, predictors, anxiety, locus of control, adaptation, self-esteem